2011
DOI: 10.1002/ibd.21606
|View full text |Cite
|
Sign up to set email alerts
|

Invasive potential of gut mucosa-derived fusobacterium nucleatum positively correlates with IBD status of the host

Abstract: This study indicates that colonization of the intestinal mucosa by highly invasive strains of F. nucleatum may be a useful biomarker for gastrointestinal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
406
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(422 citation statements)
references
References 39 publications
10
406
1
5
Order By: Relevance
“…However, colonic mucosal inflammation linked to Fn invasion and increased expression of cytokines has been suggested as a possible mechanism leading to colorectal disease [29]. Fn effectively adheres to and invades epithelial cells eliciting an immune response [27,37] and strains isolated from inflamed human biopsy material from patients with IBD exhibit a more invasive phenotype [26], while a further, recent IBD related study found invasiveness of Fn correlated with increased mRNA expression of pro-inflammatory cytokine TNF-α and IL-1β [28]. The same strain of Fn assayed in our study has been isolated from CRC tumour tissue and shown to be invasive in a CaCo-2 cell assay [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, colonic mucosal inflammation linked to Fn invasion and increased expression of cytokines has been suggested as a possible mechanism leading to colorectal disease [29]. Fn effectively adheres to and invades epithelial cells eliciting an immune response [27,37] and strains isolated from inflamed human biopsy material from patients with IBD exhibit a more invasive phenotype [26], while a further, recent IBD related study found invasiveness of Fn correlated with increased mRNA expression of pro-inflammatory cytokine TNF-α and IL-1β [28]. The same strain of Fn assayed in our study has been isolated from CRC tumour tissue and shown to be invasive in a CaCo-2 cell assay [20].…”
Section: Discussionmentioning
confidence: 99%
“…Fn is a highly invasive, gram-negative anaerobic bacterium and part of the oral and gut commensal flora [22] that has been linked to several diseases, such as periodontitis [23], appendicitis [24], Lemierre's disease [25], and inflammatory bowel disease [26]. Fn may contribute to CRC development by invading colonic mucosa and inducing local inflammation and increased expression of cytokines, leading to colorectal disease [20,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible mechanisms of action in stimulation of growth of CRC relate to the ability of Fusobacterium to invade and induce oncogenic and inflammatory responses through its unique FadA adhesin, which binds to E-cadherin and activates b-catenin signalling [96]. Potential mechanisms of function of Fusobacterium in IBD have not been described, but the invasive ability of Fusobacterium has been positively correlated with the IBD status of the host [97]. Fusobacterium provides a potential theoretical link given the increased risk of CRC associated with IBD.…”
Section: Linked To CD [105]mentioning
confidence: 99%
“…In particular, two North American studies in 2012 showed overrepresentation of Fusobacterium nucleatum in colorectal cancer tumors versus surrounding normal tissue (10,15). F. nucleatum is a highly invasive, gram-negative anaerobic bacterium and part of the oral and gut commensal microbiota that has been linked to several diseases, such as appendicitis (16) and inflammatory bowel disease (17). This bacterium may contribute to colorectal cancer development by invading colonic mucosa and inducing local inflammation and increased expression of cytokines, leading to colorectal disease (18).…”
Section: The Colon Cancer Microbiome In the Context Of Human Intralummentioning
confidence: 99%